The social impact study through the life cycle of rice production at Selangor, Malaysia - Amir Hamzah, Sharaai; Mohammad Firdaus, Masri; Somayeh, Rezaei Kalvani (Italian Association of Chemical Engineering - AIDIC, 2022)
In the effort to increase rice production in Malaysia, it may affect some parties or stakeholders, especially those involved in rice production. As this study implemented the cradle-to-grave research, the key stakeholders involved are those from the paddy plantation to the paddy process. Basically, three stakeholders are involved in rice production, which are the rice mill workers, rice farmers and the local communities. This study aims to analyze the social issues and social performances among the stakeholders involved in rice production using the Social Life Cycle Assessment (S-LCA) method. The result of this study revealed that several social issues had been identified for each of the stakeholders. For example, the social problems for the rice farmer are income, health and safety, assistance with agricultural technology development, and living standards. The total social performance of the local community, with a score of 62 % shows good performance, 59 % and 53 % for workers and farmers, offer moderate performance. Overall, based on the result, the rice farmers have the lowest social performance compared to the rice mill workers and local communities.